Seroprevalence of Hepatitis B and Hepatitis C Among Residents of Aye-Oba and Aye-Amodo in Osun State, Nigeria - Aniaguya, Regina Ngbor; Olusi, Titus Adeniyi; Simon-Oke, I. A.; Egbidi, Cynthia Adanma (Journal of Science, Technology and Innovation Research, 2025)
Hepatitis commonly known as inflammation of the liver is an infectious viral disease that affects the functioning of the liver leading to liver cirrhosis and fibrosis which if unresolved could results ultimately to death. This research was carried out to determine the prevalence of hepatitis virus B (HBV) and hepatitis virus C (HCV) and some of the associated risk factors in Aye-Oba and Aye-Amodo communities of Osun State, South West, Nigeria. A total of 411 individuals made up of 216 males and 195 females; aged between ≤10 and ≤70 were investigated using blood sampling technique. The result showed a prevalence of 3.9% and 0.0% for hepatitis B virus (HBV) and hepatitis C virus (HCV) respectively (p value 0.082). No mixed infection of HBV and HCV was recorded. The female participants had a higher prevalence of 5.6% than the males with 2.3% with no statistical difference (p>0.05). The result also indicated that participants in the age group 21-30years had the highest prevalence of 13.8% with a significant difference (p value 0.029). Sharing of shaving (barbing) kits was attributed to be the most common risk factors among the infected population. It showed a statistically significant association with hepatitis B infection (p value 0.009), with an odds ratio of 9.355 indicating that individuals who used shared shaving kits were over 9 times more likely to have hepatitis B compared to those who did not. The results of this study showed that hepatitis B virus is prevalent in Aye-Oba and Aye-Amodo communities of Osun State, and members of the communities should be discouraged from sharing shaving kits for better management and control of the infection.